Atraumatic Massive Left-sided Bochdalek Hernia in Adulthood: A Case Report - Muhamad Aizuddin Bin Ismail; Rhendra Hardy Mohamed Zainy; Syafiqah Binti Adnan (Bali Journal of Anesthesiology)
Bochdalek hernia, a rare congenital anomaly of the diaphragm, typically manifests in the pediatric population but can also occur in adults. In the adult population, it presents unique challenges in airway management due to the potential displacement of abdominal organs into the thoracic cavity, resulting in compromised respiratory function. We report the case of a 61-year-old male with a massive left-sided Bochdalek hernia, presenting with upper abdominal pain. Imaging revealed an 8.7-cm defect in the left diaphragm, resulting in herniation of the abdominal viscera into the thoracic cavity, causing a mediastinal and tracheal shift. Emergency surgical repair was conducted, requiring careful airway management, including the use of a bronchial blocker (BB) for lung isolation to safely reduce the herniated organs into the abdominal sac and repair the diaphragmatic defect. Though rare, the incidence of Bochdalek hernia in adults necessitates specific considerations for airway management due to its anatomical complexities and potential for respiratory function compromise. Successful management highlights the need for thorough preoperative planning and inter-team communication in such complex scenarios. This case demonstrates the challenges and critical considerations in managing adult Bochdalek hernia, emphasizing the importance of tailored airway management strategies and coordinated care to optimize patient outcomes in such rare disease cases.